A Review of Tax Imposition on Endorsement Activities by Influencers in Garut Regency - Alkausar, Muslim; Fauziah, Hanifah; Rismanto, Hilman; Ervianisya, Veraghina (Jurnal Wacana Ekonomi, 2024)
The increasing existence of influencers along with the increasing use of social media has become a new phenomenon because it is considered very promising in terms of the income earned. The higher the level of popularity of an influencer, the higher the endorsement rates charged. The income earned in a year by influencers from endorsement activities is indicated to exceed Non-Taxable Income (PTKP) so that it can be considered a tax object. This research aims to find out about the imposition of tax on endorsement activities by Instagram celebrities in Garut Regency. This type of research is qualitative using a critical study approach. This research analyzes primary data from interviews with five influencers who live in Garut. The results of this research show that an overview of the taxation of endorsement activities by celebgrams in Garut district can be obtained through endorsement activities carried out by influencers amounting to IDR 10,000,000 and where three influencers have a NPWP and two people who do not have a NPWP will be deducted by the agency or provider of income as VAT. This shows that endorsement activities carried out by influencers are one of the state tax activities. Compliance with tax payments for endorsement activities when compared with the provisions of the applicable tax law is still not working well, so it is hoped that the Government can clarify regulations regarding the imposition of tax on endorsement activities to avoid the loss of potential tax that could be received.